The uniformity and time-invariance of the intra-cluster metal distribution in galaxy clusters from the IllustrisTNG simulations - Vogelsberger, Mark; Marinacci, Federico; Torrey, Paul; Genel, Shy; Springel, Volker; Weinberger, Rainer; Pakmor, Rüdiger; Hernquist, Lars; Naiman, Jill P.; Pillepich, Annalisa; Nelson, Dylan (Monthly notices of the Royal Astronomical Society, 2018)
The distribution of metals in the intra-cluster medium (ICM) encodes important information about the enrichment history and ormation of galaxy clusters. Here, we explore the metal content of clusters in IllustrisTNG - a new suite of galaxy formation simulations building on the Illustris project. Our cluster sample contains 20 objects in TNG100 - a ∼(100 Mpc)3 volume simulation with 2 × 18203 resolution elements, and 370 objects in TNG300 - a ∼(300 Mpc)3 volume simulation with 2 × 25003 resolution elements. The z = 0 metallicity profiles agree with observations, and the enrichment history is consistent with observational data going beyond z ∼ 1, showing nearly no metallicity evolution. The abundance profiles vary only minimally within the cluster samples, especially in the outskirts with a relative scatter of ∼ 15 per cent. The average metallicity profile flattens towards the centre, where we find a logarithmic slope of −0.1 compared to −0.5 in the outskirts. Cool core clusters have more centrally peaked metallicity profiles (∼0.8 solar) compared to non-cool core systems (∼0.5 solar), similar to observational trends. Si/Fe and O/Fe radial profiles follow positive gradients. The outer abundance profiles do not evolve below z ∼ 2, whereas the inner profiles flatten towards z = 0. More than ∼ 80 per cent of the metals in the ICM have been accreted from the proto-cluster environment, which has been enriched to ∼0.1 solar already at z ∼ 2. We conclude that the intra-cluster metal distribution is uniform among our cluster sample, nearly time-invariant in the outskirts for more than 10 Gyr, and forms through a universal enrichment history.